PENGARUH CITRA PERUSAHAAN, STRATEGI PROMOSI, DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN MENJADI NASABAH PADA LPD DESA PAKRAMAN KESIMAN - Ni Komang Diah Komala Yuliani; Ni Putu Nita Anggraini; I Wayan Gede Antok Setiawan Jodi (VALUES, 2023)
This study aims to determine and analyze the effect of corporate image, promotion strategy, and service quality on the decision to become a customer at the LPD Desa Pakraman Kesiman. The population in this study were all LPD customers in Kesiman, totaling 14,127 customers. Sampling in this study using the Slovin formula, namely as many as 100 respondents taken from the number of customers. The analytical method used is multiple linear regression analysis. The results of the study show that corporate image, promotion strategy, and service quality have a positive and significant effect on employee performance. The promotion strategy variable has the highest beta coefficient value of 0.840. This shows that in this study the promotion strategy has a dominant influence on the increase or decrease in the decision to become a customer at the LPD Desa Pakraman Kesiman.